Demographic and behavioral responses of the White-winged Dove to human disturbances during winter in northwestern Mexico - Rubén Ortega-Álvarez; Jovani León-Aguilar; Antonio Isain Contreras-Rodríguez; Gustavo Castañeda de los Santos (Avian Research, 2022)
The simultaneous study of demography and behavior might provide a more comprehensive understanding about animal responses to anthropogenic disturbances. The White-winged Dove (Zenaida asiatica) is a frequent dweller of urban and agricultural habitats in North America, Central America, and the Caribbean. Still, research on the species is heavily biased to the USA. We analyzed the response of the species to human disturbances during winter across an urban-agricultural landscape in northwestern Mexico through a demographic and behavioral approach. We modeled the effect of disturbance types (pedestrians, cars, pavement and building cover) on the density of the species. Also, we investigated if surveillance behavior varied across the landscape by estimating and comparing perching proportion among land uses (urban grey areas, urban green areas, cropfields, shrublands). We did not detect the species within cropfields, possibly because food resources were not available for the dove during winter in this land use. Pavement cover limited species’ density, as it might reduce the surface of the preferred feeding substrates of the dove. Pedestrians and building cover increased the density of the species, as they might provide food and shelter for the dove, respectively. Surveillance behavior peaked in urban grey areas, whereas it dropped in urban green areas. Differences on threat levels, threat type, and protective cover among land uses might influence such behavioral pattern. Our approach contributes to the knowledge of the species and demonstrates that both demographic and behavioral cues provide complementary evidence for analyzing the impact of human disturbances on animals.